2014
DOI: 10.3109/00498254.2014.967824
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the potent CYP2D6 inhibitor sarpogrelate on the pharmacokinetics and pharmacodynamics of metoprolol in healthy male Korean volunteers

Abstract: 1. Recently, we demonstrated that sarpogrelate is a potent and selective CYP2D6 inhibitor in vitro. Here, we evaluated the effect of sarpogrelate on the pharmacokinetics and pharmacodynamics of metoprolol in healthy subjects. 2. Nine healthy male subjects genotyped for CYP2D6*1/*1 or *1/*2 were included in an open-label, randomized, three treatment-period and crossover study. A single oral dose of metoprolol (100 mg) was administered with water (treatment A) and sarpogrelate (100 mg bid.; a total dose of 200 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The simulation with metoprolol included only EMs for CYP2D6 to enable a direct comparison with the observed clinical data. 25 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The simulation with metoprolol included only EMs for CYP2D6 to enable a direct comparison with the observed clinical data. 25 …”
Section: Methodsmentioning
confidence: 99%
“…In both instances, the clinical DDI potential associated with CYP2D6 inhibition could not be excluded for sarpogrelate hydrochloride, and clinical studies were warranted. It was reported that the area under the curve at time t (AUC t ) and C max of metoprolol, a CYP2D6 substrate, were increased by 1.53- and 1.62-fold (multiple, 1.51- and 1.67-fold), respectively, after single or multiple coadministration with sarpogrelate hydrochloride 100 mg. 25 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarpogrelate is also glucuronidated directly by UDP‐glucuronosyltransferases and excreted into the urine and bile . Although sarpogrelate is reported to be a selective CYP2D6 inhibitor in vitro, increased systemic exposure of metoprolol (a CYP2D6 substrate) after coadministration with sarpogrelate did not show clinically relevant effects …”
mentioning
confidence: 99%
“…20 Although sarpogrelate is reported to be a selective CYP2D6 inhibitor in vitro, increased systemic exposure of metoprolol (a CYP2D6 substrate) after coadministration with sarpogrelate did not show clinically relevant effects. 21 Before the generic sarpogrelate formulation manufactured by Tianjin Hongri Pharmaceutical Co, Ltd is commercialized, the China Food and Drug Administration (CFDA) needs to confirm that it is bioequivalent to the reference drug Anplag. However, determining the bioequivalence (BE) of sarpogrelate formulations is challenging due to its limited pharmacokinetic (PK) performance and marked within-subject variability.…”
mentioning
confidence: 99%